GENERALIZED DIFFERENCE SEQUENCE SPACES OF FRACTIONAL ORDER DEFINED BY ORLICZ FUNCTIONS - Aral, Nazlim Deniz; Et, Mikail (Ankara Univ, Fac Sci, 2020)
The main purpose of this paper is to introduce the concepts of Delta(alpha)-lacunary statistical convergence of order beta (0 < beta <= 1) with the fractional order of ff and Delta(alpha)-lacunary strongly convergence of order beta (0 < beta <= 1) with the fractional order of alpha. We establish some connections between Delta(alpha)-lacunsry strongly convergence of order beta and Delta(alpha)-lacunsry statistical convergence of order beta.
Keywords: Difference sequence; statistical convergence; lacunary sequence